THU0471 The effects of tapping therapy on pain, symptom severity, dysfunctions in daily life, depression, and quality of life in patients with fibromyalgia: a randomized controlled trial. (15th June 2017) - Suh, HJ; Choi, ST; Song, J-S; Shin, SH
Abstract : Background: Fibromyalgia is a disorder characterized by chronic widespread musculoskeletal pain, often accompanied by fatigue, cognitive disturbance, psychiatric symptoms, and multiple somatic symptoms. Various pharmacological and non-pharmacological therapies have been tried in the management of fibromyalgia. However, unfortunately, management remains a challenge. Objectives: Taping therapy has been shown to be effective for pain relief in various musculoskeletal diseases. However, there was no trial for the patients with fibromyalgia. In this study, we evaluated the effects of taping therapy in patients with fibromyalgia. Methods: This study is a randomized controlled trial with 60 fibromyalgia patients. All patients were satisfied with the 2010 American College of Rheumatology diagnostic criteria for fibromyalgia. Participants were randomized to the Kinesio taping group (n=30) and to the non-elastic paper taping group (n=30) for the control. Taping experiment was performed for three weeks (twice a week) through the one-to-one meeting. Pain, symptom severity, dysfunctions in daily life, depression, and quality of life (QoL) were assessed with the widespread pain index (WPI), severity score (SS), fibromyalgia impact questionnaire (FIQ), Beck depression inventory (BDI), and the EQ-5D INDEX and EQ-5D VAS, respectively. Results: The mean ages of taping group and the control group were 54.3±12.0 years and 53.2±12.7 years, respectively, and female patients were 25/30 (83.3%) and 27/30 (90.0%) in both groups, respectively, and there were no differences between two groups in the medication use such as anti-depressants and muscle relaxants. Patients showed significant improvements after Kinesio taping therapy in pain (10.50±3.98 vs. 5.70±2.73, p <0.001), symptom severity (7.93±2.24 vs. 5.27±1.98, p <0.001), dysfunction in daily life (65.03±18.75 vs. 43.25±18.87, p <0.001), depression (18.17±8.55 vs. 13.00±6.75, p <0.001) and QoL (EQ-5D INDEX, 9.10±1.54 vs. 7.67±1.40, p <0.001; EQ-5D VAS, 38.33±24.65 vs. 56.67±27.93, p <0.001), respectively. In the control group, however, the significant improvement was detected only in pain (10.53±3.87 vs. 9.27±3.57, p =0.012). The changes before and after treatment in the Kinesio taping group revealed significant differences from those in the control group: pain ( p <0.001), symptom severity ( p <0.001), dysfunction in daily life ( p <0.001), depression ( p =0.001) and QoL ( p <0.001 and p <0.001), respectively. There was no serious adverse event. Conclusions: This study shows that Kinesio taping therapy has effects on pain, symptom severity, dysfunctions in daily life, depression, and quality of life in the patient with fibromyalgia. Taping therapy could be a useful non-pharmacological management modality for the fibromyalgia patient. Disclosure of Interest: None declared